THE PSYCHOLOGICAL SIGNIFICANCE OF SUFISM (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Sufism, through its philosophical and practical aspects, helps free individuals from ignorance and egoistic behavior, fostering positive qualities such as tranquility, patience, repentance, and love. The psychological impact of Sufism is aimed not only at improving relationships with the external world but also at restoring inner emotional balance. It deepens the relationship with oneself, others, and the Creator.